Pengaruh Harga, Produk dan Lokasi Terhadap Loyalitas Konsumen Melalui Undang-Undang Perlindungan Konsumen Pada CV. Triple Delapan Group - Anto Tulim; Zetria Erma; Monika Ellis Sukma (Yayasan Literasi Sains Indonesia, 2022)
Consumer loyalty are influenced by price, product and location factors. Companies must have competitive prices, have quality products and have a strategic location in other can be increased consumer loyalty. Price is the amount of money that has been agreed upon by prospective buyers and sellers to be exchanged for goods or services in a business transaction. Products are all things that can fulfill and satisfy human needs or desires, both tangible and intangible. Location is one of the initial activities that must be carried out before the company starts operating determining the right location will affect the company's ability to serve consumers. Consumer loyalty is a consumer's commitment to a product or service by making routine purchases more than twice. Prices that can be reached by consumers, products that are in accordance with their benefits and a location located in the city center will increase consumer loyalty. The purpose of this study was to determine or analyze the effect of price, product and location towards consumer loyalty at CV. Triple Delapan Group Medan. This research was conducted at CV. Triple Delapan Group Medan. The type of research used is descriptive quantitative research. The results showed that price, product and location had a positive and significant effect both partially and simultaneously towards consumer loyalty at CV. Triple Delapan Group Medan. The adjusted R square value of 90.7% indicates that the variable ability of price (X1), product (X2) and location (X3) affects consumer loyalty (Y) at CV. Triple Delapan Group Medan while the remaining 9.3% is the influence of other independent variables that are not explained or not examined by researchers in this study such as promotion, service quality or consumer purchase interest variables.